2012
DOI: 10.1590/s0365-05962012000400030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological profile of basal cell carcinoma in a population from Criciúma, Santa Catarina, Brazil

Abstract: Basal cell carcinoma is a local, invasive epidermal neoplasia, the most common type of which is nodular basal cell carcinoma. The objective of the present study was to evaluate the occurrence of basal cell carcinoma, characterizing its distribution in accordance with patients' age, gender, the site of the lesion and its histopathological characteristics. Anatomopathology reports of cases of basal cell carcinoma diagnosed in Criciúma, Santa Catarina, Brazil between June 2005 and June 2007 were analyzed. A descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Superficial BCC were more often found in males and preferentially developed on the cheek localization while other types preferring the nose. As in our study it was reported that nose is the most involved area with facial BCC [17]. The micronodular, nodular and superficial BCC occurred more often in males and solid and infiltrative types are more often in females.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Superficial BCC were more often found in males and preferentially developed on the cheek localization while other types preferring the nose. As in our study it was reported that nose is the most involved area with facial BCC [17]. The micronodular, nodular and superficial BCC occurred more often in males and solid and infiltrative types are more often in females.…”
Section: Discussionsupporting
confidence: 70%
“…Large studies dealing with the demographic characteristics of the histological subtypes were published only after 1995 [1,4,14]. Based on the eight largest studies previously published in the literature [1,4,5,8,[14][15][16][17], nodular BCCs comprised between 62% and 70% of all BCCs, except in the series from New Zealand, [16] in which the nodular type accounted for only 47% of all BCCs. Superficial BCCs comprised 9-17.5% and morpheaform BCCs 0.5-16.6% of carcinomas in those series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 There were only a few studies with more female than male patients. 13 It has been suggested that one reason might be that men are more often exposed to sunlight 14 and that they do not protect themselves by using sunscreen regularly. 15 Furthermore, women often wear makeup with sun protection factor.…”
Section: Discussionmentioning
confidence: 99%